Preparation of core–shell PW12@TiO2 microspheres and oxidative desulfurization performance. Issue 17 (11th April 2019) - Gao, Hongcheng; Wu, Xiaonan; Sun, Dongmei; Niu, Guiling; Guan, Jianyi; Meng, Xiangfu; Liu, Changzhan; Xia, Wandong; Song, Xiaojing
Abstract : Polyoxometalate-based heterogeneous catalyst with core–shell structure. Abstract : A polyoxometalate-based microsphere catalyst has been prepared through the one-step template method using phosphotungstic acid as the core and TiO2 as the shell, denoted as PW12 @TiO2 . Multiple characterisation methods namely FT-IR, XRD, XPS, Raman, SEM and TEM were used to characterize the resultant materials, and results indicate that the phosphotungstic acid was encapsulated into the TiO2 phase as the core to form the core–shell structure. The resultant composites were used as catalysts for the oxidative desulfurization of a model oil with H2 O2 as oxidant and acetonitrile as solvent. Catalyst PW12 @TiO2 exhibited good catalytic activity, with 99.9% S-removal of dibenzothiophene after 60 min under the optimum conditions. Leaching and recycling experiments revealed that the PW12 @TiO2 catalyst has excellent recyclability, and there was no significant decrease in S-removal after seven cycles under identical reaction conditions, which could be attributed to the fabrication of the core–shell structure, thus inhibiting the loss in the active sites.